The Relationship of Lifestyle and Consumer’s Value : In Perspective of Green Food Consumer Purchasing Behavior - Suswita Roza; Ade Octavia; Yayuk Sriayudha (Dinasti International Journal of Management Science, 2023)
The behavior of consuming green food is one form of alternative solution in an effort to maintain environmental sustainability due to consumption activities. This research aims to analyze : (1) how is the relationship between lifestyle, consumer values ??and interest in purchasing green food (2) what is the relationship between lifestyle, consumer values ??and purchasing behavior of green food consumers with purchase intention as a mediating variable, and (3) how direct relationship between interest in purchasing green food and consumer purchasing behavior. The research design uses quantitative analysis methods. The research population is consumers of food products in Jambi Province with a research sample of 200 respondents. Nonprobability sampling technique was used for research sampling. The instrument used was a research questionnaire. The data was analyzed using the Structural Equation Model (SEM/PLS) with the smart PLS tool. From the research results, it is known that lifestyle does not have a significant influence on interest and purchasing behavior of green food. Meanwhile, the perceived value of consumers has a significant influence on green food purchasing interest and behavior. Furthermore, asking consumers to purchase green food also shows a significant relationship to purchasing behavior. This research is expected to provide a substantial theoretical contribution to other researchers in fields with related interests.